(untitled) (Cadernos de Psicologia Social do Trabalho, 2014)
Work sociopsychology is not a sociopsychology applied to the working arena because work can’t be tacked only as a segment of social life. It requires a reappraisal of the theoretical and methodological frame through the concepts of activity, action and praxis. In order to achieve the objective, it is not necessary to break off part records but to revisit and develop them. In a first part, we present the foundations of work sociopsychology that we aim at developing together with other theoretical resources. In a second part, we specify how and why work is at the foundation of the subject and social units construction. Last, we address three of the work main stakes within our conceptualization: the humanization and subjectivation processes by the experience of boundaries, work as institution and as organization, and the construction of the meaning of work in its links with the Kulturarbeit.